Persistent Unresolved Inflammation in the Mecp2-308 Female Mutated Mouse Model of Rett Syndrome. (16th May 2017) - Cortelazzo, Alessio; De Felice, Claudio; De Filippis, Bianca; Ricceri, Laura; Laviola, Giovanni; Leoncini, Silvia; Signorini, Cinzia; Pescaglini, Monica; Guerranti, Roberto; Timperio, Anna Maria; Zolla, Lello; Ciccoli, Lucia; et al.
Abstract : Rett syndrome (RTT) is a rare neurodevelopmental disorder usually caused by mutations in the X-linked gene methyl-CpG-binding protein 2 ( MECP2 ). Several Mecp2 mutant mouse lines have been developed recapitulating part of the clinical features. In particular, Mecp2 -308 female heterozygous mice, bearing a truncating mutation, are a validated model of the disease. While recent data suggest a role for inflammation in RTT, little information on the inflammatory status in murine models of the disease is available. Here, we investigated the inflammatory status by proteomic 2-DE/MALDI-ToF/ToF analyses in symptomatic Mecp2 -308 female mice. Ten differentially expressed proteins were evidenced in the Mecp2 -308 mutated plasma proteome. In particular, 5 positive acute-phase response (APR) proteins increased (i.e., kininogen-1, alpha-fetoprotein, mannose-binding protein C, alpha-1-antitrypsin, and alpha-2-macroglobulin), and 3 negative APR reactants were decreased (i.e., serotransferrin, albumin, and apolipoprotein A1). CD5 antigen-like and vitamin D-binding protein, two proteins strictly related to inflammation, were also changed. These results indicate for the first time a persistent unresolved inflammation of unknown origin in the Mecp2 -308 mouse model.